Streptococcus pyogenes M1T1 Variants Induce an Inflammatory Neutrophil Phenotype Including Activation of Inflammatory Caspases - Williams, Jonathan G.; Ly, Diane; Geraghty, Nicholas J.; McArthur, Jason D.; Vyas, Heema K. N.; Gorman, Jody; Tsatsaronis, James A.; Sluyter, Ronald; Sanderson-Smith, Martina L. (Frontiers in Cellular and Infection Microbiology, 2021)
Invasive infections due to group A Streptococcus (GAS) advance rapidly causing tissue degradation and unregulated inflammation. Neutrophils are the primary immune cells that respond to GAS. The neutrophil response to GAS was characterised in response to two M1T1 isolates; 5448 and animal passaged variant 5448AP. Co-incubation of neutrophils with 5448AP resulted in proliferation of GAS and lowered the production of reactive oxygen species when compared with 5448. Infection with both strains invoked neutrophil death, however apoptosis was reduced in response to 5448AP. Both strains induced neutrophil caspase-1 and caspase-4 expression in vitro, with inflammatory caspase activation detected in vitro and in vivo. GAS infections involving strains such as 5448AP that promote an inflammatory neutrophil phenotype may contribute to increased inflammation yet ineffective bacterial eradication, contributing to the severity of invasive GAS infections.